Gerontolinguistics in China: Origin, Development, Prospects - Lijun Guo; Jiaqi Xu (Научный диалог, 2022)
The question of the formation of gerontolinguistics in China as a relatively new scientific branch for the country is considered. The relevance of the study is due to the high growth rate of the elderly Chinese population. The authors of the article offer an overview of gerontolinguistic works in China, selected on the basis of an analysis of journal articles, monographic studies, dissertations placed in Chinese libraries. It is noted that gerontolinguistics in China began its formation only in the 21st century, while in Western science the problems of working with the elderly began to be intensively studied in the second half of the 20th century. It is argued that Chinese gerontolinguistics is based on the traditions of Western science, taking into account Chinese realities. An overview of the works of Chinese scientists on gerontolinguistics is given, from 2003 to the present. It is shown that during this period, multimodal studies of the language and speech of various geront groups, including people suffering from Alzheimer’s disease, are especially actively carried out. The tasks that gerontological research solves are described, including the prevention and treatment of Alzheimer’s disease, improving the quality of life of older people, and identifying their preferences in the sociocultural sphere, for example, advertising. To solve these problems, the possibilities of artificial intelligence are actively used.